THE INFLUENCE OF LANGUAGE ENVIRONMENT IN ISLAMIC BOARDING SCHOOL ON THE ACHIEVEMENT OF ENGLISHSPEAKING SKILL - Hidayatullah, Iqbal (English Edu: Journal of English Teaching and Learning, 2023)
The language environment is a crucial factor in enhancing the language acquisition process, or the language environment consists of everything that students may see and hear in their surroundings in order to acquire a new language spontaneously. In addition, the language environment contributes considerably to improving and developing students' English-speaking abilities. Moreover, there are three fundamental components to any successful language learning: the language, the learners, and the learning method. In order to achieve effective language acquisition, the learner, the language being learned, and the language learning process, which includes the language environment, must interact ideally. However, the primary objective of employing a language environment as a learning medium is to ensure that students as information receivers absorb as much knowledge as possible in the form of information and messages. Therefore enhancing their speaking abilities. On the other hand, macro and micro contextual factors must be used to create a language environment. This research aims to find out the influence of the language environment on the achievement of English speaking skills for students in one of the dormitories under the Nurul Jadid Islamic Boarding School, namely the Natural Sciences Major dormitory, which is then applied to foreign language development institutions to meet the macro and micro requirements of the language environment for the 2021/2022 academic year. In this case, the researcher used 20 students of elementary level as samples from the population, which was selected by purposive sampling. Meanwhile, the quantitative method with a pre-experimental model applies pre-test and post-test instruments. The researcher also used an oral test in conducting his research with a total of 10 questions. The results of this study indicate that there is an influence of the language environment in improving English speaking skills for Natural Sciences Major dormitory students.